A Brief Comparison of the Chinese and United States Securities Regulations Governing Corporate Takeovers - Chun, Benjamin (Columbia Journal of Asian Law, 2019)
In May 1993, the China Securities Regulatory Commission (“CSRC”) officially released, for the first time, securities regulations governing the trading of securities on Chinese securities exchanges. Among other things, the Interim Securities Regulations specified how a company could purchase the publicly-traded shares of another company. Soon thereafter, in September of the same year, Shenzhen Bao An Enterprises (“Bao An”), a Shenzhen legal-person company, attempted the first hostile takeover of a Chinese public company by accumulating a large block of the publicly-traded shares of Shanghai Yanzhong Industrial (“Yanzhong”), a Shanghai-exchange-listed company. In response to the takeover attempt, Yanzhong planned legal action against Bao An because it believed that Bao An had not followed the Interim Securities Regulations in acquiring its block of shares of Yanzhong.